1990
DOI: 10.1002/bem.2250110405
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for calculating residential 60‐Hz magnetic fields

Abstract: A model is presented that permits the calculation of densities of 60-Hz magnetic fields throughout a residence from only a few measurements. We assume that residential magnetic fields are produced by sources external to the house and by the residential grounding circuit. The field from external sources is measured with a single probe. The field produced by the grounding circuit is calculated from the current flowing in the circuit and its geometry. The two fields are combined to give a prediction of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
2
8
0
2
Order By: Relevance
“…The other study [Mader et al, 1990] found 24-h GM ϭ 48 nT, compatible with the results from the United States, particularly considering that this was a measurement of vertical field only.…”
Section: Fields In Other Countriessupporting
confidence: 79%
See 1 more Smart Citation
“…The other study [Mader et al, 1990] found 24-h GM ϭ 48 nT, compatible with the results from the United States, particularly considering that this was a measurement of vertical field only.…”
Section: Fields In Other Countriessupporting
confidence: 79%
“…In principle, the result of a field measurement will depend on whether the meter used is sensitive to harmonics or not. Most surveys used instruments with a frequency response that would include the relevant harmonics, but some studies [Eriksson et al, 1987;Kaune and Zaffanella 1994;Mader et al, 1990;Merchant et al, 1994a,b;Hansson Mild et al, 1996;Zaffanella, 1993] measured the fundamental (50 Hz or 60 Hz) only. In practice, even a 25% harmonic content would increase the rms field by only 3%, a negligible amount in the context of this paper.…”
Section: Harmonicsmentioning
confidence: 99%
“…Field exposure covered about 70% of the animals' lives before sacrifice. The applied magnetic flux density was about one order of magnitude greater than the maximum affecting humans in residential areas in the vicinity of overhead transmission lines and around household appliances [Mader et al, 1990;Kavet et a]., 1992;Mader and Peralta, 1992;Conti et al, 19931. The choice of a magnetic flux of 5 pT met the basic methodological requirements of exposing living organisms to realistic, low-intensity magnetic flux densities likely to induce alterations, if any, that are not directly related to the very small induced current densities.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible sometimes to develop semi-analytical methods if some kind of statistical correlation exists between the magnetic field and the principal currents of the dwelling, 1~1 , ILZ, I N , and Ig. A semi-analytical method has recently been proposed [3], but it requires actual measurements of currents and magnetic fields in the dwelling.…”
Section: Hoursmentioning
confidence: 99%